Comparison of Surgical Outcome of Open versus Laparoscopic Nephrectomy - Akhtar Nawaz, Fazl e Manan, Nasrum Minallah, Romana Bibi, Khalil Ur Rehman (Journal of Rawalpindi Medical College, 2022)
Introduction: Removal of a kidney is a common surgical procedure for a longtime. The procedure was traditionally done by open surgery. Since the advent of laparoscopic surgery, nephrectomy is being done increasingly laparoscopically. The laparoscopic approach has obvious advantages. Better cosmetics, less operative time, lesser need for blood transfusions, feweranalgesia requirements, early mobility,and oral feed, early return to work,and fewerintraoperative and post-operative major complications all contribute to thesuperiority of laparoscopic nephrectomy. Objective:To compare surgical outcomesof open versus laparoscopic nephrectomy. Materials and Methods:This Retrospectives study was conducted in the Department of Urology, Institute of kidney disease, Hayatabad, Peshawar over a period of 2 years from January 2018to January 2020. Results:Our study included a total of 78 cases, 48.7% males and 51.3% females. The patient means the age of 42.69 years. 39.7% had hypertension and 19.2% had diabetes mellitus. Open nephrectomy was done in 40 patients and laparoscopic nephrectomy in 38 patients. The average operating time for open nephrectomy was 160.5 minutes and 130.9minutes for laparoscopic nephrectomy. The average blood loss during open and laparoscopic nephrectomywas 361.25ml and 59.86ml. Blood transfusion rate in open and laparoscopic nephrectomy was 55% and 10.5% (p=0.001). Overall, the post-operative complication rate was 52.5% and 21.5% for an open and laparoscopic approach. Post-operative pain was noted in 7.9% of patients in laparoscopic and 97.5% for an open approach. Fever was noted postoperatively in 26.3% and 62.5% of patients in laparoscopic and open approaches (p=0.001). The average hospital stay in the laparoscopic approach was 2.8days and 4.5days in the open approach. The mean tumor size was 5.65cm in laparoscopic while 8.1cm in the open approach. Catheter and drain removal was on average 1.18 days and 1.32days post-op day in the laparoscopic group while it was 2.35days and 2.3days post-op day in an open group, respectively. There were no per-op complications in the laparoscopic approach as compared to 2 Cases of minor IVC injury in open. Conclusion:In our study,we conclude that the laparoscopic approach for nephrectomy is far superior as compared tothe open approach and it is recommended that Laparoscopic simple and radical nephrectomy shouldbe considered a gold standard treatment. Keywords:Open nephrectomy, laparoscopic nephrectomy, tumor, HTN, DM